PENINGKATAN KETERAMPILAN MENULIS AKSARA JAWA DI SEKOLAH DASAR MELALUI METODE JIGSAW - Sunarsih Sunarsih (Ideguru: Jurnal Karya Ilmiah Guru, 2017)
The goal of the research to improve how to write javanese word skill andto improve the student learning activity. The research used jigsaw technique with play card Javanese word and their couple.Action research (PTK) is held in two sickles. As the research subject is the fifith class Elementary school .We use student activity instrument student observation,the data analyze technique the researcher use quantitative Descriptive. The Research result show that the skill how to write Javanese word before researching 0 % The research result after has been holding action research based on KKM at the 1 cycles.The result how to write Javanese word becomes 23,8% ,at sickles II become 57,1 %. So it increases how to write Javanese word .It means there is improvement I sieckles to II cyclesw as big 33,3 % .The result of the student learning activity before researching 0%,after researching becomes 23,8 % .In II sicles 57,1 % .It means there is improvement 33,3 % .So it increases before and after researching.